Integrasi Pengetahuan Tradisional dengan Pengetahuan Ilmiah untuk Pengelolaan Hutan Lestari - Herry Purnomo (Jurnal Manajemen Hutan Tropika, 2000)
Scientific knowledge faces a limitation to describe the complexity of forest ecosystem and its involved local communities. Integrating traditional and scientific knowledge is necessary to deal with this complexity. A knowledge-based system with fuzzy logic may become an alternative to complete scientific knowledge by integrating it with traditional knowledge. The paper describes how the integration can be made.